Cross-modal effect of capsaicin and pepper oleoresin on the enhancement of saltiness perception in a NaCl model solution. (June 2022) - Wang, Yang; Zhong, Kui; Shi, Bolin; Wang, Houyin; Liu, Longyun; Zhang, LuLu; Zhao, Lei; Gao, Haiyan
Highlights: Cross-model effect between "má là" and saltiness perception was investigated. Single C or P enhanced saltiness well in low NaCl concentrations water solution. Combined C + P greatly increased saltiness at moderate-to-high NaCl concentrations. Saltiness enhancement and NaCl reduction of C + P reached 37% and 26%, respectively. Offering a promising approach regarding sodium reduction strategies. Abstract: Reducing sodium scientifically and effectively without affecting the flavor and safety of food remains a challenge for food researchers. A few previous reports have shown that single capsaicin (C) and pepper oleoresin (P) modulate the saltiness perception and sodium reduction, respectively. However, there is a lack of research on whether combining the C + P has an interaction effect on saltiness enhancement. The cross-modal and interactive effect of C and P on the saltiness perception and NaCl reduction in a NaCl model solution at different concentrations (0.98 g/L ∼ 19.88 g/L) using the general labeled magnitude scale (gLMS) were investigated in this study. Results showed that single C or P had a significant saltiness enhancement effect at the low-to-medium NaCl concentration (0.98 g/L ∼ 4.44 g/L) solution. Importantly, it was confirmed for the first time that interactions of C and P can increase saltiness in a ternary water solution system with NaCl, C, and P significantly. And the combination of C and P enhanced the saltiness significantly at the moderate-to-high NaCl concentrations, and the maximum percentages of saltiness intensity enhancement and NaCl reduction reached 37.65% and 26.09%, respectively. This research not only provided valuable data regarding the modulating effect of the "má là" flavor on saltiness perception but also offer novel insights and a promising approach regarding sodium reduction strategies during the development of low-sodium food.